Pediatric dog bite outcomes: infections and scars - Benjamin Drumright; Breanna Borg; Arlene Rozzelle; Lydia Donoghue; Christina Shanti (Trauma Surgery & Acute Care Open)
Background There is little consensus on the management of dog bite victims. Few studies have examined long-term patient outcomes. This study was designed to evaluate two outcomes: infection and unfavorable scar formation.Methods A retrospective study of dog bite cases from January 2013 to May 2016 was conducted at our level I pediatric trauma center. Forty-five patients were identified who received definitive repair and had long-term follow-up for reasons other than rabies vaccination. Variables recorded were wound characteristics including presence of tissue loss, location in the hospital of the wound repair procedure, personnel performing the repair, postrepair infection, and a binary assessment of unfavorable scar formation.Results Unfavorable scarring was not significantly related to either repair location or personnel. Rate of infection was not significantly related to repair location. However, infection rate was significantly related to personnel performing the repair (p=0.002), with 8 of 11 (73%) infections after repair by emergency physicians compared with surgeons.Discussion The presence of infection was significantly related to bedside repair by emergency physicians. The data are suggestive of differences in wound preparation and repair technique between emergency department and surgical personnel. Standardizing technique could reduce infectious complications and long-term morbidity associated with repairing dog bites and other contaminated wounds. A robust and practical classification system for dog bite wounds would be helpful in stratifying these wounds for research comparison and healthcare triage.Level of evidence The level of evidence for this retrospective study is level III.